2001
DOI: 10.1001/archotol.127.1.25
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of Postoperative Nausea and Vomiting With Antiemetics in Patients Undergoing Middle Ear Surgery

Abstract: A small dose of propofol is a better antiemetic than droperidol or metoclopramide for the prevention of postoperative nausea and vomiting after middle ear surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
1
5
0
3
Order By: Relevance
“…Our study coincides with the findings of various studies of Fuji et al [6,7,[10][11][12] where complete response rate were between 78 and 86% with varying doses of granisetron having the PONV 14-22%. PONV was much less in our study although we had used granisetron in lesser dose as compared to these studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study coincides with the findings of various studies of Fuji et al [6,7,[10][11][12] where complete response rate were between 78 and 86% with varying doses of granisetron having the PONV 14-22%. PONV was much less in our study although we had used granisetron in lesser dose as compared to these studies.…”
Section: Discussionsupporting
confidence: 92%
“… 5,6 No data were available regarding the dose of ramosetron to be used in children, but the single dose of ramosetron used in this study was extrapolated from an investigation in adults. 8 …”
Section: Methodsmentioning
confidence: 99%
“…7 We have recently demonstrated that prophylactic therapy with ramosetron is more effective than granisetron for the prevention of postoperative nausea and vomiting within a 48‐hour period after anesthesia in patients undergoing middle ear surgery. 8 However, there have been no reports comparing the antiemetic efficacy of ramosetron with granisetron in children at high risk of vomiting after tonsillectomy. We designed this prospective, randomized, double‐blinded study to compare the efficacy and safety of granisetron and ramosetron for the prevention of vomiting after pediatric tonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…(23) Propofol also resulted in less PONV than sevoflurane (24) and was better than droperidol and metoclopramide. (72)(73) Pretreatment with oral clonidine enhances the antiemetic effect of propofol, preventing postoperative vomiting. (74) It has been reported that CP-122,721, a neurokinin-1 antagonist, at a dose of 200 mg orally before induction of anesthesia resulted in decreased emetic episodes compared to ondansetron.…”
Section: Treatmentmentioning
confidence: 99%